A Pseudo-Random Noise-Coded 1.35 GHz Sequential Sampling Impulse Radar System for Forefield Reconnaissance for Ice Exploration Melting Probes - Haberberger, Niklas; Stelzig, Michael; Krabbe, Lena; Hehn, Markus; Vossiek, Martin (2024 21st European Radar Conference (EuRAD), 2024)
Presented in this study is a sequential sampling impulse radar (SSIR) system with pseudo-random noise (PRN) coding designed for forefield reconnaissance for melting probes, enabling the subsurface exploration of icy moons, such as Europa and Enceladus. Characterized by simple hardware and a compact form factor, the developed multi-channel SSIR utilizes pseudo-random noise sequences to effectively enhance the signal-to-noise ratio (SNR). Demonstrating exceptional sensitivity and performance, a prototype system was tested on the Langenferner glacier in Ital